Vocational Education: The New Development and Change in the Adaptive Curriculum of Learning Model - Barliana, M. Syaom; Alhapip, Leli; Ana, Ana; Rahmawati, Yulia; Muktiarni, Muktiarni; Dwiyanti, Vina (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
The challengesÂ with vocational education are that graduates are not prepared to work because they do not have the competencies required by the business industry. The graduates from vocational high school have a high unemployment rate because the curriculum is not in line with the needs of the business industry and also graduates standards are quite low. The research aimed to find a solution to these problems. One of the solutions that could be explored was by implementing an integrated learning curriculum model in vocational education. Adaptive curriculum policy is a curriculum that is modified and adapted when necessary, and each educational unit is allowed to innovate. The research method used was a systematic literature review on journals from the last ten years relating to adaptive curriculum and vocational education. The result showedÂ that learning with an integrated curriculum model explored the greatest potential of teachers and students to innovate and improve the quality of learning independently. This promotes the development of working opportunities in the business and industrial sectors, creating high-quality of vocational school graduates with a high degree of skills and characters to become professional workers that are ready to compete in the global era and also creating confident graduates who have the entrepreneurial capacity.Â